The Status of e-Administration in Hungary – Are We on the Right Track? - Veszprémi, Bernadett (Public Governance, Administration and Finances Law Review, 2017)
The goal of this study is to define (or find out) where Hungary currently stands in the development of e-Administration solutions. The issue is more topical than ever, as infocommunications became an integral part of our daily lives, affecting both the private and public sectors, and changing our ways of working – thus, it requires our understanding. When it comes to the public sector, however, striking changes can only be achieved if the entire process of public administration is (or would be) changed. The goals are clear: work should be faster, as it would result in satisfied clients, cut costs and more efficient procedures. The question to ask now is where Hungary stands in this endeavour. Are we on the right track?